Activation of Agrp neurons modulates memory-related cognitive processes in mice - Zimmer, Marcelo R. (Pharmacol Res, 2019)
Hypothalamic Agrp neurons are critical regulators of food intake in adult mice. In addition to food intake, these neurons have been involved in other cognitive processes, such as the manifestation of stereotyped behaviors. Here, we evaluated the extent to which Agrp neurons modulate mouse behavior in spatial memory-related tasks. We found that activation of Agrp neurons did not affect spatial learning but altered behavioral flexibility using a modified version of the Barnes Maze task. Furthermore, using the Y-maze test to probe working memory, we found that chemogenetic activation of Agrp neurons reduced spontaneous alternation behavior mediated by the neuropeptide Y receptor-5 signaling. These findings suggest novel functional properties of Agrp neurons in memory-related cognitive processes.